Peran dan Kuasa Kyai Dalam Pendidikan Spiritual Lansia di Pondok Sepuh Payaman Magelang - Dwi Agustina (ARISTO, 2021)
This article examines the role and power of the religious leader in  spiritual education in the elderly cottage. The religious leader became a figure that has a central position in the boarding school. The central position of the religious leader, encouraging the community and elderly students to obediant on the orders and their decisions. To review this article, used a qualitative descriptive method. The process of collecting data using observations and interviews in depth. The findings of this study that the role of religious leader in spiritual education as 1) teacher in spiritual education; 2) motivators and advisers in the implementation of spiritual education; 3) Role model for elderly students. In conducting spiritual education, religious leader holds full power over the materials, methods, and timing of learning. Religious leader also has full power in influencing personality and behavior students. All the orders and decisions of the religious leader become the grip for students in daily life. Obedientet to the religious leader  is done  to avoid any, that are feared will not get blessings. The religious leader with the mastery of religious sciences and the higher levels of virtuous than the students, be able to hold the students to be better.